DIGITIZATION OF CADASTRAL DATA AND THEIR INTERACTIVE USE (Web of Technology: Multidimensional Research Journal, 2024)
The digitization of cadastral data and its interactive use in the Fergana region is a critical development for enhancing land management systems. The relevance of this topic lies in its alignment with global trends toward modernizing land administration, improving transparency, and ensuring more efficient governance. By incorporating technologies such as Geographic Information Systems (GIS), remote sensing, and digital mapping, the region stands to benefit from more accurate land records, reduced transaction times, and increased security of land rights. This shift not only facilitates smoother land administration processes but also supports sustainable land use, urban planning, and agricultural management. The study discusses the potential socio-economic impacts of digitizing cadastral data, with a focus on the Fergana region, while also addressing the challenges of implementation, including infrastructure and digital literacy. The findings underline the importance of sustained investment in technology and training to fully realize the potential of digital cadastral systems.